Analisis Metode Sistem Pendukung Keputusan Pemilihan Waktu Terbaik Perubahan Harga Dinamis Hotel - Pramana, Surya; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2019)
Research discusses the decision support system method which is considered to be used for selection of the best time of hotel dynamic price change. The research was conducted by analyzing the results and process of applying the AHP, TOPSIS, SAW, and SMART methods in sample case of selection of the best time of hotel dynamic price change. The conclusions obtained from this research, the AHP and SAW methods have advantages in the consistency of the matrix and the calculation process compared to other methods. The writer recommends combining the AHP and SAW methods in decision support system of best time selection of hotel dynamic price change by considering matrix validity and ease of calculation process, with the hope that the decisions produced are more accurate with a less risk of errors.